Songs That Merge With Prayer: The Theological Meaning of Qui Bene Cantat, Bis Orat in the Formation of Faith at the Solafide Sereh Christian Church - Pandi, Seprianti Elisabet; Polhaupessy, Yustinus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study examines the theological meaning of the expression qui bene cantat, bis orat in worship singing practices and its contribution to the formation of the faith of the GKI Solafide Sereh congregation due to shifts in contemporary church music practices that have the potential to place singing more as an aesthetic expression than as a prayer that is experienced theologically. This study uses a qualitative approach with a contextual theology paradigm. Data was collected through participatory observation in worship services, in-depth interviews with liturgical ministers and congregants, and analysis of the lyrics of hymns used in worship services. The analysis was conducted using a theological-hermeneutical approach, viewing singing as a locus theologicus, or a space where faith is experienced and lived out. The results of the study indicate that hymns are understood by the congregation as a form of personal and communal prayer that brings about an experience of closeness to God, especially when supported by theological lyrics that are relevant to life experiences. Hymns function as an affective, relational, and transformative medium that shapes individual faith while strengthening communal faith identity. This study concludes that in the context of GKI Solafide Sereh, singing with sincerity not only deepens prayer, but also shapes a living and sustainable faith in the practice of church life.